Back to back converter control technique using MATLAB - Mohd Amri, Lai Din (2010)
Back to back converter circuit model is a cascade circuit that a combination of AC to DC rectifier and DC to AC inverter. The AC input source firstly will converted to DC by using a rectifier and then will converted back to AC by using an inverter. Some application that using back to back converter is such as variable speed wind turbine that employ wound rotor induction generator and also HVDC transmission system. Generally, this project can be divided into three parts that is modeling rectifier station, inverter station and the controller for both station